2020
DOI: 10.3390/microorganisms8091348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactic Acid Bacteria on the Lipid Profile of Bean-Based Plant Substitute of Fermented Milk

Abstract: Biological processes of legumes may change their nutritional value of lipids, but there is no research on the fatty acid profile and their position distribution in fermented beverages obtained from germinated bean seeds. The present study aimed to determine the effect of fermentation by Lactobacillus strains on the fatty acid profile and their positional distribution in triacylglycerols of beverage obtained from germinated bean “Piękny Jaś Karłowy” (Phaseolus vulgaris) fermented by Lactobacillus strains. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 31 publications
4
42
0
2
Order By: Relevance
“…The fat present in legumes does not contain cholesterol [34]. While examining the lipid profile of white bean seeds of the "Piękny Jaś Karłowy" variety, Ziarno et al [36] showed that the dominant fatty acid was linolenic acid (C18:2 n-6c), amounting to 39.23% of the total pool. Other unsaturated acids present in significant amounts were α-linolenic acid (23.23% of all fatty acids) and oleic acid (17.58% of all fatty acids).…”
Section: Nutritional and Health Value Of Bean Seeds And Bean-based Beveragesmentioning
confidence: 99%
See 4 more Smart Citations
“…The fat present in legumes does not contain cholesterol [34]. While examining the lipid profile of white bean seeds of the "Piękny Jaś Karłowy" variety, Ziarno et al [36] showed that the dominant fatty acid was linolenic acid (C18:2 n-6c), amounting to 39.23% of the total pool. Other unsaturated acids present in significant amounts were α-linolenic acid (23.23% of all fatty acids) and oleic acid (17.58% of all fatty acids).…”
Section: Nutritional and Health Value Of Bean Seeds And Bean-based Beveragesmentioning
confidence: 99%
“…Significant differences have been observed in the distribution of fatty acids in TAGs depending on the variety of beans and other legume seeds [33,37,38,40,41]. In his diploma thesis, Ziarno et al [36] described the positional distribution of fatty acids in the TAG molecules in the lipids of bean seeds of the "Piękny Jaś Karłowy" variety (Table 1). Ryan et al [37] determined the content of α-linolenic, linoleic, and oleic acids in kidney beans to be, respectively, 45.69%, 26.04%, and 11.97% of all fatty acids.…”
Section: Nutritional and Health Value Of Bean Seeds And Bean-based Beveragesmentioning
confidence: 99%
See 3 more Smart Citations